Determinant of Indonesia’s Gdp : Corporate Sukuk as Mediator - Maula Arsyadanil Haq; Salwa Nabila Nihaya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze the impact of the Money Supply and Inflation on Gross Domestic Product (GDP) mediated by Corporate Sukuk. The research method utilizes descriptive quantitative approach using secondary data that accessed through the websites of the BPS, KEMENDAG, BI, and OJK from 2011 to 2020. The information investigation in this study uses path anaysis and sobel test with eviews 12 application to analyze the impact of free factors on subordinate variable. This study indicate that in the first regression analysis the money supply has a significant positive effect on corporate sukuk. Meanwhile, inflation has a significant negative effect on corporate sukuk. In the second regression analysis, the effect of money supply, inflation, and corporate sukuk on GDP shows that the money supply and corporate sukuk have a significant positive effect on GDP. Meanwhile, inflation has no significant effect on GDP. The results of the Sobel test state that corporate sukuk mediate the relationship between the effect of money supply and inflation on GDP.